An Improved Method for Establishing Accurate Water Potential Levels at Different Temperatures in Growth Media - Aujla, Iqbal S.; Paulitz, Timothy C. (Frontiers in Microbiology, 2017)
NaCl, KCl, or PEG (polyethylene glycol) - amended potato dextrose broth (PDB), and potato dextrose agar (PDA) are essential for pure culture studies of water stress on fungi. Direct information on the actual water potential (WP) of this salt-amended PDB and PDA is lacking. Much fungal research in the past calculated WP of these salt-amended growth media by adding the WP of their constituents taken from individual salt dilution studies. But the WP of any complex solution will be modified by the level of synergism between its solutes. This study presents evidence of change in NaCl concentration due to synergism for attaining the same level of WP in NaCl solution, and NaCl amended PDB and PDA. The relation between WP and temperature and WP and salt concentration is also modified depending on the number of solutes in a growth medium. The WP of PEG-amended PDB increases with rising temperature, while that of NaCl/KCl amended PDB and PDA decreases with the increase of temperature. These results can be useful for doing pure culture studies on the biology and modelling the growth of air, water, and soil-borne fungi important in the food and agriculture industry and, terrestrial and aquatic ecosystems.